The Impact of Innovative Culture on Employee Creativity: The Mediating Role of Intrinsic Motivation and the Moderating Role of Team Support in Photo Studios in Bandar Lampung City - Nirmala Tantri; Febrianty; Ayu Nursari (Citakonsultindo, 2026)
This study aims to examine the effect of innovative culture on employee creativity with intrinsic motivation as a mediating variable and team support as a moderating variable in photo studios in Bandar Lampung City. This research uses a quantitative approach with a survey method involving 133 employees from 11 photo studios. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results show that innovative culture has a positive and significant effect on employee creativity and intrinsic motivation. Intrinsic motivation also has a significant effect on employee creativity and acts as a mediating variable in the relationship between innovative culture and creativity. In addition, team support is proven to moderate the relationship between intrinsic motivation and employee creativity, where higher team support strengthens this relationship. These findings indicate that employee creativity is influenced by organizational, psychological, and social factors. Therefore, organizations need to develop an innovative culture, enhance intrinsic motivation, and build a supportive team environment to improve employee creativity